KAJIAN ETNOFARMAKOLOGI TUMBUHAN OBAT OLEH MASYARAKAT DI KECAMATAN TANTA KABUPATEN TABALONG PROVINSI KALIMANTAN SELATAN - Yani Mulyani; Ninda Ryana; Nita Selifiana (Jurnal Insan Farmasi Indonesia, 2019)
Indonesia is a country with abundant biodiversity. Forests in Borneo are some of the most biodiverse forests in Indonesia although the efforts of the use of traditional medicines from plants have long been known by the community today. Inventory the type, part, way of use, dose, the purpose of how to obtain, the aspect of knowledge and utilization of medicinal plants used by the community in the village of Tanta Hulu and Warukin District, Tabalong District, South Kalimantan. Exploratory surveys and observational methods, through interviewing of semi-structures with 56 respondents using questionnaires including disease names, local names of plants, parts utilized, how to acquire, How to make them, assessment aspects of knowledge and utilization. the results of the study were 28 species of medicinal plants that belong to the 22 families used by the community, with The most numerous plant families are Asteraceae. The Plant parts used are leaves, roots, stems, bulbs, fruits, and flowers. The processing of plant parts include boiled, pounded, shredded and eaten directly. A total of 56 respondents assessed aspects of medicinal plants' knowledge and utilization